A geomorphological characterisation of river systems in South Africa: A case study of the Sabie River. (June 2018) - Eze, Peter N.; Knight, Jasper
Abstract: Fluvial geomorphology affects river character, behaviour, evolution, trajectory of change and recovery potential, and as such affects biophysical interactions within a catchment. Water bodies in South Africa, in common with many other water-stressed parts of the world, are generally under threat due to increasing natural and anthropogenic influences including aridity, siltation and pollution, as well as climate and environmental change. This study reports on a case study to characterise the geomorphology of different river systems in South Africa, with the aim of better understanding their properties, controls, and implications for biophysical interactions including water quality, biodiversity (aquatic and riparian), and human activity within the catchment. The approach adopted is based on the River Styles ® framework (RSF), a geomorphology-based approach developed for rivers in New Zealand and Australia, but applied here for the first time to South Africa. Based on analysis of remote sensing imagery, SRTM-2 digital topographic data and field observations on sites through the entire river system, six geomorphic elements were identified along the Sabie River, northeast South Africa (gorge, bedrock-forced meander, low-moderate sinuosity planform controlled sand bed, meandering sand bed, low sinuosity fine grained sand bed, and floodouts), using the RSF classification scheme and based on the RSF procedural tree of Brierley and Fryirs (2005). Previous geomorphological studies along the Sabie River have shown that different reaches respond differently to episodic floods; we use these data to link river geomorphological character (as defined by the RSF) to the hydrodynamic conditions and processes giving rise to such character. This RSF approach can be used to develop a new management approach for river systems that considers their functional biophysical behaviour within individual reaches, rather than considering them as homogeneous and uniform systems. Highlights: Water bodies in South Africa are generally under threat. Geomorphology of the Sabie River was characterised. River Styles ® framework (RSF) approach was applied for the first time in South Africa. Six geomorphic elements were identified along the Sabie River. RSF can be used to develop a new management approach for river systems.